2021
DOI: 10.1186/s12891-020-03903-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of reverse total shoulder arthroplasty for primary and secondary fracture care: mid-term outcomes in a single-centre experience

Abstract: Background The introduction of reverse total shoulder arthroplasty (RSA) as a treatment option in complex proximal humeral fractures, has significantly extended the surgical armamentarium. The aim of this study was to investigate the mid-term outcome following fracture RSA in acute or sequelae, as well as salvage procedures. It was hypothesized that revision RSA (SRSA) leads to similar mid-term results as primary fracture treatment by RSA (PRSA). M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…However, Seidel et al demonstrated that delaying RTSA for >4 weeks, in the setting of an acute PHF is associated with higher short-term revision rate and dislocation rate compared to earlier intervention (<4 weeks) [ 91 ]. Schwartz et al [ 93 ] compared the outcomes of RTSA in an acute setting versus RTSA for fracture sequela or salvage situation in a retrospective study with a minimum follow up of 2 years and minimum age of 60 years. They compared the outcomes of 42 RTSA done for acute PHF (<10 days) with 26 RTSAs done for delayed fracture care or revision indication (10 failed ORIF, 12 failed non-operative treatment, and 4 failed HA).…”
Section: Special Considerations For Rtsa For Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Seidel et al demonstrated that delaying RTSA for >4 weeks, in the setting of an acute PHF is associated with higher short-term revision rate and dislocation rate compared to earlier intervention (<4 weeks) [ 91 ]. Schwartz et al [ 93 ] compared the outcomes of RTSA in an acute setting versus RTSA for fracture sequela or salvage situation in a retrospective study with a minimum follow up of 2 years and minimum age of 60 years. They compared the outcomes of 42 RTSA done for acute PHF (<10 days) with 26 RTSAs done for delayed fracture care or revision indication (10 failed ORIF, 12 failed non-operative treatment, and 4 failed HA).…”
Section: Special Considerations For Rtsa For Fracturesmentioning
confidence: 99%
“…Several retrospective cohort studies have shown improved PROM scores and ROM outcomes after a salvage with a RTSA [ 94 , 95 , 96 ]. Furthermore, primary RTSA in an acute setting is associated with slightly better PROM, ROM and less complication rate compared to RTSA after failed osteosynthesis [ 93 , 97 , 98 , 99 , 100 ].…”
Section: Special Considerations For Rtsa For Fracturesmentioning
confidence: 99%
“…Proximal humeral fractures are among the most common injuries in the population above the age of 65 years [ 1 , 2 ]. Often, it occurs as a result of low-energy trauma, such as falls onto the outstretched limb or the shoulder itself [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%